HUBUNGAN ASUPAN MIKRONUTRIEN DENGAN KADAR HEMOGLOBIN PADA WANITA USIA SUBUR (WUS) - Oky Nor Sahana; Sri Sumarmi (Media Gizi Indonesia, 2015)
Women in reproductive age is a group that are more susceptible to anemia. Anemia is caused by a deficiency of various nutrients in the body which existence affects each other and it can lower the immune system then increased risk of morbidity. The aim of this study was to analyze the relationship between intake of iron, vitamin A, vitamin B2, vitamin B6, vitamin C, folic acid, and zinc with hemoglobin level among women in reproductive age. This cross sectional study was conducted in 9 subdistricts in Probolinggo and subjects were 71 people selected by simple random sampling using secondary research data in 2014. Micronutrients intake data obtained by 24 hours recall method then compared to RDA. Hemoglobin level measured by Hemocue. Data was analyzed using the Pearson correlation test. The result showed the average of hemoglobin level was 12.01 ± 1,24 g/dl and anemia prevalence was 42.25%. Statistical analysis showed that vitamin A intake is correlated to hemoglobin level (p = 0.015; r = 0.287). Further analysis is done by dividing respondents into two groups, anemic and not anemic to analyze the difference of the average of micronutrients intake. The sufficient level of vitamin A and vitamin B6 were adequate (≥ 77% RDA), but only vitamin A that significantly associate to hemoglobin level. Keywords: micronutrient intake, hemoglobin level, Women in reproductive age